INDOMARET VS ALFAMART : THE BATTLE FOR STORE ATMOSPHERE SUPREMACY - Wardana, M. Azka Kesuma; Octavini, Nanda Andreas; Nurbaiti, Seni (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
Indomaret and Alfamart, two retail giants in Indonesia, compete fiercely for market share. This study focuses on the Competition in the in-store experience, known as "store atmosphere." Store atmosphere is a key factor in the retail business that can influence customer behavior and satisfaction" Store atmosphere is a key factor in the retail business that can influence customer behavior and satisfaction. This study aims to understand the comparison of consumers' assessment of store atmosphere in the two major outlets. A total of 384 respondents provided ratings for 13 store atmosphere attributes, and the results were analyzed using the Importance Performance Analysis (IPA) method. The results showed that both Indomaret and Alfamart have similar challenges in creating a satisfying store atmosphere for customers. Some attributes such as store layout, display, exterior, and interior have performance that is rated low by customers. Both companies need to take corrective actions to meet customer expectations for these attributes. Both companies should understand their customers' preferences and focus on attributes that have a higher priority in creating a satisfying store atmosphere, while maintaining good quality performance on attributes that are already adequate. In conclusion, competition between Indomaret and Alfamart remains fierce, with store atmosphere being an Importance factor in winning over customers.